DEVELOPMENT OF ASSESSMENT SYSTEM IN SCHOOL EDUCATION - K. G. Kozhabayev; Dalinger Viktor Alekseyevich; Zykrina Symbat Zhumabayevna (Scientific Journal of Pedagogy and Economics, 2020)
. This article discusses the history of assessment as an important component of the content of education. Updates in the content of education in the Republic of Kazakhstan are directly related to changes in the assessment system. Therefore, this problem is one of the urgent problems. The article analyzes the interpretation of the definitions "assessment" and "mark" in various pedagogical and psychological studies of scientists. The advantages and disadvantages of the traditional assessment system are considered while investigating the prerequisites for the introduction of criteria-based assessment. The five-point assessment system introduced in 1944 is characterized by its simplicity, clarity, consistency and versatility. But long-term practice of teachers also revealed its shortcomings. The authors highlight some of the main shortcomings of this system of assessment and give detailed explanations. In conclusion, the recommendations of various researchers on the modernization of the five-point assessment system are given. Conclusions are made about the necessity of transition to the model of criteria-based assessment including the quality of traditional assessment and assessment based on criteria.